2019
DOI: 10.1080/14686996.2019.1629836
|View full text |Cite
|
Sign up to set email alerts
|

Ability of hydrogen storage CeNi5-xGax and Mg2Ni alloys to hydrogenate acetylene

Abstract: Hydrogen storage properties and reactivity for hydrogenation of acetylene in a series of CeNi 5-x Ga x (x = 0, 0.5, 0.75, 1, 1.25, 1.5) alloys and Mg 2 Ni were determined and compared. The structure of CeNi 5 (CaCu 5 type) was maintained up to CeNi 3.5 Ga 1.5 when Ni was replaced by Ga. The replacement facilitated hydrogenation absorption by creating larger interstitial spaces through expansion of the lattice, allowing CeNi 4.25 Ga 0.75 to absorb the greatest proportion of hydrogen atoms among the alloys under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…Specifically, H-abs reacts only weakly with alkynes. Soga et al examined the hydrogenation of ethylene (C 2 H 4 ) over LaNi 5 H n and reported that the catalytic activity increased with increases in the amount of hydrogen storage, in agreement with our previous reports. However, Soga’s work also showed that H-abs reacted with C 2 H 4 to form ethane (C 2 H 6 ) without the involvement of gas-phase hydrogen . Therefore, the role of H-abs in the catalytic reaction remains uncertain.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Specifically, H-abs reacts only weakly with alkynes. Soga et al examined the hydrogenation of ethylene (C 2 H 4 ) over LaNi 5 H n and reported that the catalytic activity increased with increases in the amount of hydrogen storage, in agreement with our previous reports. However, Soga’s work also showed that H-abs reacted with C 2 H 4 to form ethane (C 2 H 6 ) without the involvement of gas-phase hydrogen . Therefore, the role of H-abs in the catalytic reaction remains uncertain.…”
Section: Introductionsupporting
confidence: 69%
“…In fact, some hydrogen storage alloys have been applied as catalysts, such as in the hydrogenation of carbon dioxide. 8−10 Our group has also reported the hydrogenation of alkynes [acetylene (C 2 H 2 ) and propyne (C 3 H 4 )] over RENi 5 (RE = rare earth)-type hydrogen storage alloys (specifically, CeNi 5−x Al x , 11 CeNi 5−x Ga x , 12 and Er-Ni 5−x Al x 13 ) and has shown that hydrogen absorption by these materials further promotes alkyne hydrogenation. 11−13 This prior work demonstrated that H-abs activates the adsorbed alkyne and adsorbed hydrogen (H-ad) on the surface since the rate of hydrogen desorption from the bulk alloy is slower than the catalytic hydrogenation of alkynes on the hydride surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermetallic compounds (IMCs) exhibit a wide range of attractive functions and characteristics that are not attainable in ordinary elemental metals, such as a shape memory effect, 1 superconductivity. 2 and hydrogen absorption 3 They also possess excellent properties for hydrogenation catalysis, such as those demonstrated in Heusler alloys, 4,5 Zintl phases, 6 and hydrogen absorbing alloys. 3,7,8 Quasicrystals 9 are complex IMCs with aperiodic structures that often exhibit five-fold symmetry.…”
Section: Introductionmentioning
confidence: 99%
“… 2 and hydrogen absorption 3 They also possess excellent properties for hydrogenation catalysis, such as those demonstrated in Heusler alloys, 4,5 Zintl phases, 6 and hydrogen absorbing alloys. 3,7,8 Quasicrystals 9 are complex IMCs with aperiodic structures that often exhibit five-fold symmetry. Crystalline approximants, on the other hand, are periodic crystals having a similar chemical composition and atomic 10,11 and electronic structures 12 closely related to quasicrystals.…”
Section: Introductionmentioning
confidence: 99%